Epistemologi Hadis-Hadis dalam Naskah Tanbih al-Masyiy - Edi Safri; Sarmida Hanum; Juman Tio Aris Putra; Nandi Pinto; Nabil El Mumtaza Arifin (Universitas Islam Negeri Imam Bonjol Padang, 2024)
The study of manuscripts or manuscripts is generally seen from a philological perspective, but when we look more deeply at each religious manuscript using arguments in the form of the Qur'an and Prophetic Hadith. Therefore, in the manuscript of tanbih al-masyiy, the hadith of the prophet is found in the form of pieces without meeting the standards and methods of writing the correct hadith according to the agreed upon hadith scholars, in addition to the status and quality of the hadith is also unknown. Therefore, this article aims to examine and analyze the writing and quotation of the hadith, then perform takhrij, and finally look at the quality of the hadith used. The method used by the author is a qualitative research method with a literature approach. As for studying the hadith, the author uses the takhrij method through the words or phrases of the matn of the hadith which is prioritized with the phrases that are considered garib, using the hadith search encyclopedias software, namely through: 1) al-Maktabah al-Syamilah, version Shawwal 1444 AH, 2) Jawami' al-Kalim version 4,5 3) Hadith Soft and 4) In addition, the book al-Mu'jam al-Mufahras li-Alfaz al-Hadis al-Nabawiy compiled by A.J. Wensinck (ed.) was also used. The results of the reading that the author found were 62 citations, while the attribution of the hadith to the Messenger of Allah from the Companions was found to be 20 traditions, 7 traditions were mawquf traditions, and the names of the narrators were mentioned in 2 traditions only. The attribution is written with several variations of سلم و عليه لهل صلى, often summarized with the acronym صلعلم and even with ص alone. There are also unequivocal attributions to the Prophet such as و رد / فـقـد و رد / وقال / فقال. The takrij of the hadith conducted found that the text was only a snippet of the original text. In addition, there is also an additional redaction of the matan from the narrator. The sanad is referred to based on the assessment results in the application. Finally, the quality of the hadith varies from sahih, sahih/hasan (scholarly), sahih/daif (scholarly), daif, daif/maudhu' (scholarly), and maudhu'/la ashla lah.